Fermentasi Larutan Glukosa Untuk Produksi Etanol Dengan Teknik Immobilisasi Sel Saccharomyces Cerevisiae - Yeni Rizki; Syaiful Bahri; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Ethanol or ethyl alcohol (C2H5OH) is an organic compound that is very important in the chemical industry and has many benefits in human life. One way of making ethanol is fermentation. Arising problem in the fermentation process is the inhibition of the ethanol product that will damage the structur of the plasma membrane and cause protein denaturation will result in inhibited microbial growth and lower productivity. In this research, the fermentation process of glucose solution with cell immobilization technique to obtain ethanol at higher levels. This research is aimed to study the process of making ethanol with cell immobilization technique and determine the effect of the initial sugar concentration and fermentation time of the acquisition of ethanol. Fermentation takes place in batch reactor with a volume of 2 liters of fermentation medium, heavy beads of 20% (w/v), pH 5,0. The fermentation process of glucose solution was done at various variation of fermentation time i.e 24, 36, 48, 60, 72, 84 and 96 hours and also various variations of concentration of glucose as the intial sugar i.e 100 mg/ml, 125 mg/ml and 150 mg/ml. The process was stired at speed of 200 rpm and temperature of fermentation at room temperature (25 – 30oC). Ethanol concentrations were analyzed using Gas Chromatography. From the result was obtained that the maximum fermentation process is show at glucose concentration of 150 mg/ml and fermentation time of 60 hours with ethanol concentration of 5,149% (v/v) or 40,647 mg/ml.Keywords : Ethanol, Fermentation, Immobilized Cells, Saccharomyces cereviceae.